Freshwater planarians (Platyhelminthes, Tricladida) from the Palearctic section of the African continent: new records, with the description of a new species - Harrath, Abdul Halim; Sluys, Ronald; Merzoug, Djemoi; Yacoubi-Khebiza, Mohamed; Alwasel, Saleh; Riutort, Marta (Zootaxa, 2012)
On the basis of extensive surveys, an update is provided on the diversity, taxonomy, anatomy, and geographic distributionof five species of North African freshwater planarians, including the description of one new species. The new species Dug-esia tubqalis Harrath & Sluys, sp. nov. is mainly characterized by the following features: an elongated penis surroundedwith two penial folds at its base, the dorsal one bigger than the ventral ; an atrium divided into a male and common atriumby a kind of non-muscular ridge; a terminal expansion of the ejaculatory duct just before it opens at the tip of the penispapilla. The record of Dugesia sicula represents the first fully documented record of a naturally sexual, diploid (2n=18)population in North Africa. The first finding of Polycelis nigra on the African continent is documented. The genus Polyce-lis is recorded here with two species, Polycelis nigra and Polycelis felina. We also noted the presence of Schmidtea polychroa, which is widespread in Europe and introduced in North America.